Supporting Indian farmers: Price support or direct income/investment support? - Ashok Gulati; Tirtha Chatterjee; Siraj Hussain (Indian Council for Research on International Economic Relations (ICRIER), 2018)
With increasing farm distress in the wake of falling farm prices in 2017, the State Government of Madhya Pradesh (GoMP) came out with an innovative scheme called Bhavantar Bhugtan Yojana (BBY), a price deficiency payment (PDP) scheme, to support farmers. It covered eight Kharif crops in 2017-18 and promised to pay the difference between their minimum support prices (MSPs) and their market prices (averaged for MP and at least two other adjoining states). The scheme was abruptly withdrawn in March 2018 just before the commencement of rabi-marketing season. In this paper we review the scheme, the challenges it posed in its implementation during kharif 2017-18, but more importantly compute its likely costs, if it is scaled at the national level. Under the assumption of MSP being equal to 1.5 times A2+FL cost, and excluding the quantum of paddy and wheat procured at MSP and sugarcane at FRP/SAP, we find that compensation of Rs 56,518 crore will have to be made if market prices are 10 percent lower than MSP, Rs 1.13 lakh crore when market prices are 20 percent lower than MSP and Rs 1.69 lakh crore when prices are 30 percent lower than MSPs. We find that the scheme is prone to manipulation by traders and lower level mandi functionaries, and may end up helping them more than the farmers, despite best intentions of the Government. We also highlight that MSPs based on cost plus pricing, completely ignoring the demand side, will lead to major distortions in the agri-marketing system. The resulting efficiency losses may far exceed the support that government is intending to extend to farmers. Therefore, wisdom lies in thinking rationally now, and support farmers through less distortionary policies. It may be through investing heavily in marketing infrastructure, storage and food processing, changing the APMC Act to allow direct buying from farmer producer organizations (FPOs) bypassing the archaic mandi system, or direct income (investment) support (DIS) on per hectare basis, as recently announced by Telangana and Karnataka. DIS is easier to implement, more transparent, more equitable, crop neutral, and less distortionary than the PDPs/BBY type schemes. DIS, if launched at the national level will cost Rs 1.97 lakh crore under the assumption that all farmers get Rs 10,000/ha irrespective of what crops they are growing and whom they are selling. The cost will be much lower if farmers, who have sold their paddy and wheat at MSP to government agencies and sugarcane at FRP/SAP to sugar mills, are excluded from this DIS payment. This would be on comparable basis to the costs under PDP schemes, and yet less distortionary.
Keywords: Q18; Q13; Q11; 330; Bhavantar Bhugtan Yojana; Price Deficiency Payment; Direct Income Support; Madhya Pradesh; Telangana